Attribution in local newsletters and approve anonymous sources: Al-Sumaria satellite channel - a model - Fakhri Hassan, Muhassad (Al-Adab Journal, 2019)
The newsletters issue has raised interest of academic and public levels, especially in the light of internal and external accelerating developments, because of the magnitude events on one hand, and their importance on the other hand. This situation has increased the importance of news bulletins and made them in the center of focus attention and public follow-up. In large so the TV station had given more attention of the newsletters by continuous developing its contents and presenting the style. The activing of radio need's news production achievement in new style and changing values of production ​​in the record time. satellite channels did their best to improve the contents of publications in the level of (information, opinion, analysis) on one side, on the other sie they try achieve to scoop broadcast in rapid. On the format level, they tried to employ modern technologies continuously to increase public's dazzling and attractions.In spile of the many details that affect the efficiency of news bulletins and their distinction in terms of format and content, the news sources will remain one of the basic in achieving it, this factor mad great compete among channels to obtain sources which are "credible, strong attractive and spread to make media message more effective And in the recipient.